Protrusion of the Rod Electrode in the Electrospinning Process - Jan Valtera; Lucie Vysloužilová; Jiří Komárek; Josef Skřivánek; Petr Žabka; Jaroslav Beran; David Lukáš (Journal of Nanotechnology)
The paper focuses on the influence of the protrusion of the rod electrode on critical voltage in the DC electrospinning process. On the testing and industrial DC electrospinning devices, electrodes of any kind are extended towards the counter electrode. This provides the maximal, that is, supercritical, electric field intensity on the spinning-electrode orifice that is found to be higher than on the other supplementary parts. The principal study and experiments with basic apparatus were carried out and presented by Taylor in 1966. This study is focused on the arrangement closely related to the design of the real electrospinning device with respect to the safety and technological aspects. Results of the carried out experiments of the rod spinning-electrode are compared with the electrostatic simulation and analytical calculation. The presented effect of the electrode protrusion on the potential difference and the critical field strength introduces valuable information for the designers of electrospinning machines as well as for the setting up of the optimal technological parameters for producing modern nonwoven textile products.